The Effect of Methodology in Determining Disparities in In-Hospital Mortality of Trauma Patients Based on Payer Source. Issue 2 (March 2015) - Berg, Gina M.; Lee, Felecia A.; Hervey, Ashley M.; Hines, Robert B.; Basham-Saif, Angela; Harrison, Paul B.
<x xml:space="preserve">Abstract</x> A retrospective registry review of adult patients admitted to a Level I trauma center sought to determine whether results regarding in-hospital mortality associated with payer source vary on the basis of methodology. Patients were categorized into 4 literature-derived definitions (Definition 1: insured and uninsured; Definition 2: commercially insured, publicly insured, and uninsured; Definition 3: commercially insured, Medicaid, Medicare, and uninsured; and Definition 4: commercially insured, Medicaid, and uninsured). In-hospital mortality differences were found in Definitions 2 and 3, and when reclassifying dual-eligible Medicare/Medicaid into socioeconomic and age indicators. Variations in methodology culminated in results that could be interpreted with differing conclusions.